2016
DOI: 10.1007/s10404-015-1697-7
|View full text |Cite
|
Sign up to set email alerts
|

A new extended Reynolds equation for gas bearing lubrication based on the method of moments

Abstract: equation has been used to model slider bearings. In the theory of lubrication, the continuum description is assumed and inertial terms are negligible (Reynolds 1886). A pressure equation can then be obtained with one dimension less than the Navier-Stokes (NS) equations. However, as modern read-write heads are typically floating 50 nm or less above the moving disk, the characteristic length scale involved is comparable to the molecular mean free path, , and the continuum assumption is no longer considered to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For all DSMC simulations in this study, the gas was assumed to be argon and the variable hard sphere (VHS) model was employed. Previous theoretical and numerical studies , 2011Gu et al 2010;Gu, Zhang & Emerson 2016) have indicated that the results from the R26 equations using Maxwell molecules and the DSMC simulations using a VHS model are in close agreement with each other. Bird's no-time-counter (NTC) scheme (Bird 1994) has been employed for calculating the collision probabilities in a cell.…”
Section: Description Of the Direct Simulation Monte Carlo Methodsmentioning
confidence: 54%
“…For all DSMC simulations in this study, the gas was assumed to be argon and the variable hard sphere (VHS) model was employed. Previous theoretical and numerical studies , 2011Gu et al 2010;Gu, Zhang & Emerson 2016) have indicated that the results from the R26 equations using Maxwell molecules and the DSMC simulations using a VHS model are in close agreement with each other. Bird's no-time-counter (NTC) scheme (Bird 1994) has been employed for calculating the collision probabilities in a cell.…”
Section: Description Of the Direct Simulation Monte Carlo Methodsmentioning
confidence: 54%
“…Then, according to the analysis in Eq. (19), the pressure rise in the rough bearing is smaller than that in the smooth bearing. Meanwhile, the bearing load capacity becomes smaller in the rough bearing and the load center moves to the entrance of channel.…”
Section: A Roughness Effect Under a Variety Of Pitch Anglesmentioning
confidence: 83%
“…1 Recently, a new extended Reynolds equation based on the regularized 13 moment equations and the lubrication theory has been derived for gas slider bearings, but it can only be applied for the Knudsen number up to unity. 19 Therefore, it is essential to establish a generalized gas film lubrication equation derived from the Boltzmann equation for flows at arbitrary values of the Knudsen number. [20][21][22][23][24][25] The generalized Reynolds equation for rarefied gas flows has been established by Fukui and Kaneko 21 and Cercignani, Lampis, and Lorenzani, 25 where the mass flow rates (MFRs) of the fundamental Poiseuille and Couette flows in the lubrication film are obtained based on gas kinetic equations such as the linearized Bhatnager-Gross-Krook (BGK) kinetic equation 26 for arbitrary Knudsen numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations on porous gas bearings were mainly focused on the bearing performance with neglecting the influence of shaft rotation 6‐8 . However, with the increasing in rotational speed, the aerodynamic effect in the gas film clearance becomes highly significant 9 . Then, the high‐speed porous gas bearings are often used as hybrid bearings whose operation not only depends on the aerostatic but also on the aerodynamic effect.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, with the increasing in rotational speed, the aerodynamic effect in the gas film clearance becomes highly significant. 9 Then, the high-speed porous gas bearings are often used as hybrid bearings whose operation not only depends on the aerostatic but also on the aerodynamic effect. Some researchers 10,11 have studied the characteristics of conventional orifice-restricted aerostatic bearings with the consideration of aerodynamic effect.…”
Section: Introductionmentioning
confidence: 99%